A STUDY OF METABOLIC SYNDROME IN THE RURALPOPULATION OF HARYANA. (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Metabolic Syndrome (MS) is the clustering of risk factors for cardiovascular disease. It is estimated that the burden due tocardiovascular disease (CVD) will markedly increase in developing countries particularly in the Indian subcontinent.Because both under nutrition and over nutrition are seen simultaneously in developing countries, the double burden ofdiseases makes the situation more difficult. The study included 100 subjects of the age group 20 -60 yrs attending the OPDof MMIMSR. The cross-sectional study was done for a period of 3 months from the month of January 2011 to April 2011.Simple Random sampling methods was adopted for the selection of subjects. According to NCEP definition, maximumoverall percentage of MS was 20.5% and gender specific for males and females was 30.1% and 26.7% respectively.Prevalence of obesity and the metabolic syndrome has shown a rapid rise in developing countries in the past few decadesand has led to increased risk of CVD and consequent morbidity and mortality.